UPAYA PENINGKATAN KEMAMPUAN BEBICARA SISWA MELALUI PENERAPAN METODE STUDENT FACILITATOR AND EXPLAINING PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS V SDN 11 CILEGON - Aizahwa Nur Safitri; Desty Endrawati Subroto; Muhammad Baehaki; Laily Fauziyah; Ririn Maharani (Jurnal Padamu Negeri, 2025)
Students lack of speaking ability is the background of this research. The goal is to improve students speaking skills through learning Indonesian by using the Student Facilitator and Explaining method. The approach used in this research is a descriptive qualitative approach to explain and explain in more detail related phenomena and examine more deeply from relevant references. Based on the observation, population of this study is 50 students in grade V of SDN 11 Cilegon. Students were more enthusiastic about learning to speak after using the method applied by the researcher, especially when explaining the picture. Thus, The implementation of the SAFAE method. method to students provides positive and significant results in the Indonesian language learning process. In conclusion, the implementation of this method in Indonesian language learning consistently improved student performance across sessions, as reflected in the increasing percentage of successful learning outcomes.